(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
The imbalance between the crop production and population growth is currently the major issue in southern Ethiopia. To feed the growing population, increasing the production of food through growing more crop types in the same field as an intercropping is the right strategy. The current study was aimed at evaluating the effect of sorghum-legume intercropping and its residual effect on yield of sorghum. The land equivalent ratio was calculated for sorghum intercropped with pigeon pea and cowpea. Intercropping sorghum with pigeon pea and cowpea increases the land productivity as its Land Equivalent Ratio is greater than 1. In both cases, the land equivalent ratio is greater than 1 indicating the benefits of intercropping. The residual effect of sorghum intercrop with legumes was evaluated on the yield of sorghum. Although there was no statistically significance differences on yield and yield component of sorghum, sorghum planted on the plot of pigeon pea and cowpea sole has 44.6% and 27.8% yield advantage relative to sorghum alone respectively. Planting sorghum under sorghum-cowpea intercropped condition increase the yield of sorghum by 41.8%. The result also shows 74.0% sorghum yield change was observed when planted after intercropped condition of sorghum with pigeon pea. The productivity of sorghum also increases when planted on the plot of sole legume. The current finding in general shows that legume crops contributed to the yield of sorghum either intercropped with legume or grown up using residual contribution of legumes after a year. Therefore, for maximum sorghum production farmers in the area should plant either as intercrop or after residual effect of legumes. Int. J. Agril. Res. Innov. Tech. 9(2): 62-66, December 2019